Gender Diversity Moderates the Effect of Good Corporate Governance on the Financial Performance of Sharia and Conventional Banking Companies Registered with the OJK - Sesri Sellina; Etty Zuliawati Zed (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the Gender Diversity Moderates the Influence of Good Corporate Governance on the Financial Performance. This study examines Sharia & Conventional Banking Companies registered with the OJK in 2021-2024. The population in this study is all Sharia & Conventional Banks registered with the OJK in 2021-2024, totaling 106 Sharia & Conventional Banks. The sampling technique used in this study was purposive sampling, which uses specific criteria to select samples. Therefore, the sample size for this study was 85 companies over the four years of the study. Data collection carried out in this study was by using literature studies and documentation. Testing of the research hypothesis was carried out using the Econometric Eviews 12 approach. The results of the study indicate that independent commissioners, audit committees, managerial ownership, and internal audit have no effect on financial performance. Gender diversity also does not moderate the influence of independent commissioners, audit committees, managerial ownership, and internal audit on financial performance.